Strategic Adaptation and Resilience: Islamic Education's Response to Colonialism in Indonesia - Firmansyah, Rizky; Azzahra, Fatimah; Rosyidah, Amiliya Nur; Supriyatno, Triyo (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This study examines the strategic responses of Islamic educational institutions—particularly pesantren and madrasah—to the socio-political structures imposed by Dutch colonial rule in Indonesia. Employing a qualitative historical-analytical methodology, the research draws on primary archival sources and secondary historiographical literature to explore how Islamic education functioned as a site of resistance and adaptation. The findings reveal four dominant themes: first, the modernization of Islamic education as a form of intellectual resistance, wherein reformist organizations like Muhammadiyah integrated secular subjects and structured pedagogies to cultivate an intellectually competitive Muslim generation; second, the consolidation of traditional institutions as cultural fortresses, as seen in Nahdlatul Ulama’s efforts to strengthen pesantren and preserve religious orthodoxy; third, the mobilization of women through education, particularly through the efforts of ‘Aisyiyah, as a strategy for moral reform and national identity formation; and fourth, the internalization of nationalist values through character education, positioning pesantren and madrasah as crucibles of civic responsibility and anti-colonial consciousness. These findings underscore that Islamic education during the colonial period was not merely a religious endeavor but a multidimensional force for cultural resilience and political mobilization. Theoretically, the study contributes to the discourse on education as a nonviolent strategy of resistance under colonialism, while practically offering insights for contemporary education policy in Indonesia. However, the study is limited by its reliance on secondary sources, which may overlook local variations and grassroots dynamics. Further research incorporating oral histories and archival case studies is recommended to enrich our understanding of the lived experiences and post-colonial legacies of these institutions.